2017
DOI: 10.1080/21505594.2017.1365216
|View full text |Cite
|
Sign up to set email alerts
|

Novel Influenza D virus: Epidemiology, pathology, evolution and biological characteristics

Abstract: In 2011, a new virus was isolated from pigs with influenza-like symptoms and subsequently also from cattle, which are the main reservoir of the virus. It is similar to Influenza C virus (ICV), a (predominantly) human pathogen, causing respiratory disease in children. Since the virus is unable to reassort with ICV (and based on several other criteria as discussed in the text) it is now officially named as Influenzavirus D (IDV), a new genus of the Orthomyxoviridae. We summarize the epidemiology, pathology and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 70 publications
2
104
0
5
Order By: Relevance
“…To our knowledge, this is the first report of identification of IDV in western Canada. IDV was initially identified in swine in the United States, and then was found to be prevalent in cattle of the United States, Luxembourg, Ireland, France, Japan and China (Flynn et al, ; Mekata et al, ; Snoeck et al, ; Su, Fu, Li, Kerlin, & Veit, ). IDV may be an emerging pathogen in Canadian cattle; or, on the other hand, the lack of Canadian reports before may be due to the unavailability of a diagnostic assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first report of identification of IDV in western Canada. IDV was initially identified in swine in the United States, and then was found to be prevalent in cattle of the United States, Luxembourg, Ireland, France, Japan and China (Flynn et al, ; Mekata et al, ; Snoeck et al, ; Su, Fu, Li, Kerlin, & Veit, ). IDV may be an emerging pathogen in Canadian cattle; or, on the other hand, the lack of Canadian reports before may be due to the unavailability of a diagnostic assay.…”
Section: Discussionmentioning
confidence: 99%
“…IDV was also recently identified in sheep and goats (Quast et al, ). Although there is evidence that IDV can infect humans, whether it can cause disease is unclear at this point and the risk of zoonosis is considered to be low (Su et al, ). Preliminary evidence showed that IDV could be potentially associated with BRD (Mitra et al, ; Ng et al, ), and our study provided additional evidence for the role of IDV in BRD as its detection was significantly associated with BRD in single variable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about IDV have been raised since its discovery, and it has now been found worldwide, particularly in cattle (Hause et al, ; Su, Fu, Li, Kerlin, & Veit, ). We first reported the identification of IDV in western Canada, and the prevalence was 13.8% in nasal swabs and tracheal washes from cattle with BRD (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Viruses that are commonly implicated include bovine herpesvirus-1 (BHV-1), bovine viral diarrhea virus (BVDV), bovine respiratory syncytial virus (BRSV) and parainfluenza 3 virus (PI3V) [3]. Cattle are considered the major IDV reservoir but understanding the possible role of IDV in bovine respiratory disease (BRD) is one of the main focuses of research studies concerning this virus [4,5]. BRD is a complex pathology causing economic losses and it is linked with microbial pathogens, host, environmental and animal management factors.…”
Section: Introductionmentioning
confidence: 99%